2019
DOI: 10.1111/anae.14553
|View full text |Cite
|
Sign up to set email alerts
|

Neostigmine‐induced weakness after sugammadex

Abstract: We would like to challenge Naguib and Kopman's editorial assertion [1] that Kent et al.'s study on neostigmine-induced weakness in awake volunteers [2] 'probably has little or no

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Recently, a report indicated that rescue administration of sugammadex (200 mg) after administration of neostigmine (50–70 mg/kg) for NMB reversal can result in a paradoxical reduction in the TOF ratio. This is because complete removal of rocuronium from the neuromuscular junction by sugammadex may lead to a desensitized block, similar to a phase-2 block, due to excessive intrasynaptic acetylcholine made available after high-dose neostigmine administration [ 52 ].…”
Section: Use Of Sugammadex In a Special Clinical Situationmentioning
confidence: 99%
“…Recently, a report indicated that rescue administration of sugammadex (200 mg) after administration of neostigmine (50–70 mg/kg) for NMB reversal can result in a paradoxical reduction in the TOF ratio. This is because complete removal of rocuronium from the neuromuscular junction by sugammadex may lead to a desensitized block, similar to a phase-2 block, due to excessive intrasynaptic acetylcholine made available after high-dose neostigmine administration [ 52 ].…”
Section: Use Of Sugammadex In a Special Clinical Situationmentioning
confidence: 99%
“…Maintaining deep NMB improves surgical working conditions in selected laparoscopic procedures [10][11]. Sugammadex can rapidly reverse NMB, regardless of the depth of the block, and is associated with a lower risk of postoperative residual curarization after extubation [12][13][14]. A recent study showed that spontaneous recovery of NMB was an independent risk factor for PPC in intermediate-to-high risk patients undergoing abdominal surgery [15].…”
Section: Introductionmentioning
confidence: 99%